Determinants of short birth interval among child-bearing age women in the Gedeb Hasasa district of the West Arsi zone, Ethiopia - Yosef, Tewodros; Debela, Degfachew; Shifera, Nigusie (Frontiers in Medicine, 2023)
Background Short birth intervals have been linked to higher rates of fetal loss, prenatal mortality, and poorer child survival. Therefore, for countries like Ethiopia that have a population policy intended at reducing fertility, understanding the level and factors influencing birth spacing is crucial in order to apply appropriate intervention. This study aimed to assess the prevalence and determinants of the short birth interval among child-bearing age women in the Gedeb Hasasa district of the West Arsi zone, Ethiopia. Methods A community-based cross-sectional study was conducted from 20 July to 20 August 2018. A multistage sampling method was used. Face-to-face interviews were conducted to gather data. The collected data were entered into Epi Data version 3.1 and later exported to SPSS version 21 for analysis. Logistic regression was used to identify factors associated with the short birth interval. The level of significance was declared at a p-value of <0.05. Results A total of 714 women participated, with a 98% response rate. The median birth interval length was 32 months. The prevalence of the short birth interval was 50.4%. After adjusting for confounding variables, being a rural resident [AOR = 2.50, 95% CI (1.52, 4.09)], having an illiterate husband [AOR = 4.14, 95% CI (2.15, 8.45)], breastfeeding duration for 7–12 months [AOR = 3.16, 95% CI (1.95, 5.13)] and 13–23 months [AOR = 2.45, 95% CI (1.52, 3.95)], sex of the prior child [AOR = 0.63, 95% CI (0.45, 0.88)], and previous child alive [AOR = 0.20, 95% CI (0.14, 0.96)] were the determinants of short birth interval. Conclusion and recommendation One in every two women practiced short birth intervals. The median birth interval duration was 32 months, which is below the minimum standard recommended by the WHO duration for the birth interval, which is 33 months. Short birth intervals were determined independently by residence, husband education, breastfeeding time, previous child’s sex, and previous child’s survival. Therefore, increasing women’s awareness of the ideal birth interval should be done through community health professionals and health developmental armies.